(untitled) (Boletim de Geografia, 2019)
This paper aims to determine the configuration of the drainage system and water storage in Wanda Glacier, located in King George Island (KGI), South Shetland Islands (61°54’ – 62°16’S and 57°35’ – 59°02’W), Antarctic Peninsula, using data obtained by 100 MHz GPR (Ground Penetration Radar) survey. This site is characterized by accelerated retraction and melting processes as consequence of a recent regional warming. Topography data were used to generate transversal and longitudinal sections and a three-dimensional model (DSM) of the glacier surface. The GPR system was able to deliver information about the internal structure and about the meltwater drainage configuration. GPR internal reflections are attributed to basal water films and intraglacial and subglacial water channels in the Wanda Glacier. The abundance of internal diffractions is considered an indicative of temperate ice with high liquid water content. Similar internal structures are observed in other glaciers in KGI. The application of GPR to Wanda Glacier study showed the dielectric contrasts, internal layering and englacial structure, glacier bed condition and the distribution of individual channels in the glacier and the englacial and subglacial routing of meltwater. Probably the configuration of a subglacial drainage and water liquid exerts an influence on the sediment evacuation by basal meltwater, subglacial erosion and the proglacial deposition pattern.